Do Mendeley reader counts indicate the value of arts and humanities research?. (September 2019) - Thelwall, Mike
Mendeley reader counts are a good source of early impact evidence for the life and natural sciences articles because they are abundant, appear before citations, and correlate moderately or strongly with citations in the long term. Early studies have found less promising results for the humanities and this article assesses whether the situation has now changed. Using Mendeley reader counts for articles in 12 arts and humanities Scopus subcategories, the results show that Mendeley reader counts reflect Scopus citation counts in most arts and humanities as strongly as in other areas of scholarship. Thus, Mendeley can be used as an early citation impact indicator in the arts and humanities, although it is unclear whether reader or citation counts reflect the underlying value of arts and humanities research.